Analysis of Indonesian Language Proficiency Test in High School Students' Reading Section - Humaira, Hera Wahdah; Agustiani, Tanti; Suparman, Fauziah (Universitas Pendidikan Mandalika, 2024)
This study aims to identify and evaluate high school students' scores in Sukabumi City on the reading section of the Indonesian Language Proficiency Test. The research method used a descriptive with a qualitative approach. The subjects of this research are students from SMA Muhammadiyah in Sukabumi City, consisting of 5 classes, namely classes X, XI A, XI B, XII IPS, and XII IPA. The instrument used was an Indonesian Language Proficiency Test sheet containing 40 questions. The data analysis technique used was a qualitative descriptive method to describe the results of the students' proficiency data. The results showed that the initial abilities of the five classes in high school in Sukabumi City, namely classes X, XI A, XI B, XII IPS, and XII IPA, obtained an average score of 170, while the abilities in the second test of the five classes in high school in Sukabumi City, namely classes X, XI A, XI B, XII IPS, and XII IPA, obtained an average score of 194. The results of the data from the two test sessions, the scores of the UKBI test in the reading category, showed that from the five classes, the results for test 1 show an average student ability score of 170 with a